Economics - Some Influences of Foreign Demand on the Domestic Oil Situation - E. B. Swanson (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1932)
Frequent reference has been made to the increased domestic gasoline demand recorded for 1931. This increase was in the neighborhood of 7,000,000 bbl. Although smaller relatively than that to which the oil industry had become accustomed by virtue of the experience of preceding years, the increase was of substantial amount, particularly at a time when any increase at all could be regarded with eminent satisfaction. Less has been said, however, of the 18,000,000 bbl. decline in gasoline shipments to territories and foreign countries. When the loss of business outside the United States is combined with the domestic increase, there results a net loss of some 11,000,000 bbl. in total gasoline demand. The gain of 2 per cent in domestic sales gives way to a loss of 2.5 per cent in total domestic and foreign sales. The United States actually has been losing ground in the international gasoline market since 1924, when shipments from this country equaled 72 per cent of the gasoline shipments from the leading gasoline-producing countries of the world. A loss in relative standing was recorded with each succeeding year. As long, however, as gasoline shipments showed an actual increase, the loss in relative standing was of little concern. Foreign producing centers annually supplied an increasing share of the foreign gasoline markets, but, until the past year, the demand abroad continued to increase at a pace which could accommodate all of the increased output of foreign plants and yet require increasing quantities from the United States. It was not until 1931 that the various factors were combined so as to produce an actual and substantial decrease in the foreign demand for United States gasoline. Consumption in foreign countries generally declined, while the output of foreign refineries and the foreign manufacture of substitute fuels continued to increase. From our own viewpoint, this meant a loss of some 18,000,000 bbl. of gasoline business in foreign countries, one-half of it probably due to the lowering in foreign demand and the other half to the increased output of foreign refineries and the increased utilization of substitute fuels.